Supporting Accessible Care for Pregnant Women Experiencing IPV in Peru: A Thematic Analysis of Barriers to and Facilitators of Women’s Help Seeking - Carney, Jessica R. (Journal of family violence, 2024)
PurposePerinatal intimate partner violence (IPV) is a prevalent problem in Peru, but no evidence-based interventions have been developed to address the needs of Peruvian pregnant women exposed to IPV. The current qualitative study examined existing resources in Lima, Peru for IPV-exposed pregnant women, barriers to women’s access to resources, and how to make a new intervention for these women accessible and responsive to their needs.MethodUsing thematic analysis, the study analyzed qualitative focus groups data from healthcare providers (N = 11) and pregnant women (N = 14, 50% of whom had experienced perinatal IPV) in Lima.ResultsWomen used word of mouth from other women to determine which community resources were trustworthy. Obstacles to resource utilization included IPV-related barriers, emotional barriers, and lack of knowledge about, access to, and trust in community and legal resources. Participants discussed that future interventions for IPV-exposed pregnant women should provide information to bolster women’s resilience across the lifespan, such as childhood education about safe sex and gender equality, and education in adulthood about safety planning for IPV, healthy relationships, and maternal health and infant care. To improve resource accessibility, participants described the importance of fostering trust among women and healthcare providers, providing childcare, transportation, and mental and physical health services at little to no cost.ConclusionStudy findings have important implications for mental health supports, women’s access to information, and broader social efforts aimed at reducing perinatal IPV in Peru, especially the role of accessible community resources in fostering women’s resilience.